Competency-based education of specialists at a medical university - D. N. Isakova; O. A. Rusakova; K. E. Zavedensky; E. S. Shchegolenkova; D. N. Dolganov; M. V. Lyapina; K. A. Vikulova; T. N. Vasilkova; I. M. Petrov (Кардиоваскулярная терапия и профилактика)
The training of medical specialists needs systemic transformation. Educational organizations must create conditions for developing research competencies and innovative activities among future healthcare, as well as implement transversal formats for attracting and managing talented youth at all stages of professional development. To create a passport of educational program competencies and describe the results of educational activities, the "Competency Standard" database has been developed. The aim was to classify groups and categories of competencies, including the subject’s competencies (both educational and project), the competencies of activity development, and transversal competences applicable in any type of educational and project activities. Project-based training for students makes it possible to form following priority competencies in medicine and pharmacy: analytical, research, professional, communicative, digital, managerial and entrepreneurial. Project-based learning and new educational formats are used as an transversal technology in the implementation of innovative programs, the target audience of which is students with increased educational potential, claiming a portfolio of high-quality competencies.